Investigating the effect of reflexology on the breast milk volume of preterm infants' mothers - Atena Mohammadpour; Mahboubeh Valiani; Alireza Sadeghnia; Sedigheh Talakoub (Wolters Kluwer Medknow Publications, 2018)
Background: Reflexology is an interventional method which may lead to improved breast milk. Because the mechanism of milk production is complex, detailed research is required on the relationship between lactation and reflexology. Therefore, the aim of the present study was to determine the effect of reflexology on the volume of milk among mothers with premature infants. Materials and Methods: This clinical trial was conducted among 50 mothers with premature infants in two groups of 25 patients admitted to the neonatal intensive care unit of Alzahra and Shahid Beheshti hospitals of Isfahan, Iran from August 2015 to November 2015. The patients were selected through convenience sampling method and divided into control and reflexology groups through random allocation. In the reflexology group, massage of the sole of the foot and foot was done in six sessions. The control group received regular breastfeeding training. Data were analyzed using descriptive and inferential statistics. Results: Repeated-measures analysis of variance test indicated that the mean volume of breast milk in reflexology group (F = 44.002, p < 0.001) and control group (F = 43.09, p < 0.001) differed significantly at different times. Independent t-test showed that the mean increase in milk volume from day 1 to day 5 after the intervention compared to before the intervention was significantly higher in the reflexology group compared to the control group 1days after the intervention (t=5.25, p<0.001), 2 days after the intervention (t= 4.81, p<0.001), 3 days after the intervention (t=3.55, p=0.001), 4 days after the intervention (t= 2.98, p=0.004), 5 days after the intervention (t= 2.50, p=0.020). Conclusions: The results indicate that reflexology is effective on the volume of milk of mothers, and this low-cost and easy procedure can be used along with regular lactation training.